PENGEMBANGAN DAN INOVASI PASAR HUTAN BAMBU TO`KUMILA - Ferayanti Boas Gallaran; Israel Padang; Semuel Yakobus Padang; Bergita Gela Saka; Gidion Aryo Nugraha Pongdatu; Ariyen Duri (Jurnal Pengabdian Masyarakat Khatulistiwa, 2026)
ABSTRACTSustainable tourism development increasingly focuses on integrating nature-based tourism (ecotourism) and cultural heritage (cultural tourism). To'Kumila Bamboo Forest Market in Tonga Riu Village, North Toraja Regency, holds strong ecological and cultural potential; however, its management faces challenges including limited physical infrastructure, lack of MSME product innovation, and underutilized digital marketing. This community service program aims to enhance tourism appeal and local economic capacity through nature- and culture-based market innovations. The methodology employed a participatory approach, community empowerment, and educational interventions involving market managers, 16 local MSME actors, villagers, and tourists. Program implementation comprised socialization, hospitality training, physical site enhancement using bamboo-based green architecture, implementation of a unique bamboo token ("seng") transaction system, local culinary and craft product diversification, and digital marketing mentoring via social media platforms. The results demonstrated an increase in community capacity, a more aesthetic and eco-friendly market environment (zero-plastic packaging), the creation of an authentic experience tourism concept, and functional digital marketing channels expanding tourist reach. This initiative confirms that integrating Community-Based Tourism (CBT), ecotourism, and digital technology effectively fosters creative economic self-reliance and environmental sustainability in rural areas.Keywords: Community-Based Tourism, Creative Economy, Digital Marketing, Ecotourism, To'Kumila Bamboo Forest Market, Tourism Village, North Toraja.ABSTRAKPengembangan pariwisata berkelanjutan kini berfokus pada integrasi wisata alam (ecotourism) dan kearifan budaya (cultural tourism). Pasar Hutan Bambu To’Kumila di Lembang Tonga Riu, Kabupaten Toraja Utara, memiliki potensi ekologis dan budaya yang tinggi, namun pengelolaannya masih menghadapi tantangan seperti fasilitas yang terbatas, minimnya inovasi produk UMKM, dan belum optimalnya promosi digital. Kegiatan pengabdian masyarakat ini bertujuan untuk memperkuat daya tarik wisata dan kapasitas ekonomi lokal melalui inovasi pasar berbasis alam dan budaya. Metode yang digunakan adalah pendekatan partisipatif, community empowerment, dan edukatif yang melibatkan pengelola wisata, 16 pelaku UMKM, masyarakat desa, serta wisatawan. Tahapan kegiatan meliputi sosialisasi, pelatihan hospitality, penataan fisik kawasan berbasis arsitektur hijau berbahan bambu, pengembangan sistem transaksi unik berbasis token bambu (seng), diversifikasi produk kuliner dan kerajinan lokal, serta pendampingan digital marketing via media sosial. Hasil pengabdian menunjukkan adanya peningkatan pengetahuan masyarakat, terwujudnya tata kelola pasar yang lebih estetik dan ramah lingkungan (zero-plastic packaging), terbentuknya pengalaman wisata (experience tourism) yang autentik, serta tersedianya media promosi digital yang memperluas jangkauan wisatawan. Kegiatan ini membuktikan bahwa integrasi Community-Based Tourism (CBT), ekowisata, dan pemanfaatan teknologi digital efektif dalam mendorong kemandirian ekonomi kreatif serta pelestarian lingkungan di kawasan pedesaan.Kata kunci: Community-Based Tourism, Ekowisata, Ekonomi Kreatif, Pasar Hutan Bambu To’Kumila, Toraja Utara.